2005
DOI: 10.1037/0033-2909.131.5.635
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attractiveness and Health in Western Societies: A Review.

Abstract: Evidence from developed Western societies is reviewed for the claims that (a) physical attractiveness judgments are substantially based on body size and shape, symmetry, sex-typical hormonal markers, and other specific cues and (b) physical attractiveness and these cues substantially predict health. Among the cues that the authors review, only female waist-to-hip ratio and weight appear to predict both attractiveness and health in the claimed manner. Other posited cues--symmetry and sex-typical hormonal marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
208
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(219 citation statements)
references
References 142 publications
(357 reference statements)
6
208
3
2
Order By: Relevance
“…Indeed, factors such as body mass index (BMI), body fat and waist-to-hip ratio (WHR) have been shown to correlate with attractiveness judgements (Singh, 1993;Tovée, Reinhardt, Emery, & Cornelissen, 1998;Weeden & Sabini, 2005), and are predictive of both health and fertility (Singh & Singh, 2011). For instance, slender figures with a low WHR and large breasts are often rated as more attractive and considered for relationships (Singh & Young, 1995), furthermore these features have been shown to correlate with high fecundity as measured by levels of sex hormones (Jasieńska, Ziomkiewicz, Ellison, Lipson, & Thune, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, factors such as body mass index (BMI), body fat and waist-to-hip ratio (WHR) have been shown to correlate with attractiveness judgements (Singh, 1993;Tovée, Reinhardt, Emery, & Cornelissen, 1998;Weeden & Sabini, 2005), and are predictive of both health and fertility (Singh & Singh, 2011). For instance, slender figures with a low WHR and large breasts are often rated as more attractive and considered for relationships (Singh & Young, 1995), furthermore these features have been shown to correlate with high fecundity as measured by levels of sex hormones (Jasieńska, Ziomkiewicz, Ellison, Lipson, & Thune, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This possibility was systematically examined in this study. As measurements of BMI, WHR and chest size are strong predictors of attractiveness (Singh, 1993;Tovée et al, 1998;Weeden & Sabini, 2005), when assessing regional body dissatisfaction we included both objective measurements and subjective ratings of body parts.…”
Section: Introductionmentioning
confidence: 99%
“…By using composites and controlling for expression, Kramer and Ward (2010) demonstrated that health could be accurately read from the face, even when some of these cues were minimal due to the removal of colour and external facial features. While the use of composites minimises fluctuating asymmetries, a potential cue to health (Weeden and Sabini 2005), it makes any directional asymmetries even more apparent.…”
mentioning
confidence: 99%
“…Ghirlanda & Enquist, 1998, 2003. As for WHR, it's possible that men's preference for relatively small WHRs (Furnham et al, 2005;Henss, 1995;Singh, 1993;Streeter & McBurney, 2003;Weeden & Sabini, 2005) is the result of a shiftlike process, given that larger WHRs correlate with poorer health and reproductive fitness (e.g., Bray, 1992;Price et al, 2006;Rexrode et al, 1998;Wass et al, 1997). However, experimental demonstrations of this effect are as of yet absent from the research literature.…”
Section: Discussionmentioning
confidence: 81%
“…A woman's WHR is negatively correlated with measures of health and reproductive fitness (e.g., Bray, 1992;Price, Uauy, Breeze, Bulpitt, & Fletcher, 2006;Rexrode et al, 1998;Wass, Waldenström, Rössner, & Hellberg, 1997) and ratings of physical attractiveness by both women and men (e.g., Furnham, Petrides, & Constantinides, 2005;Henss, 1995;Singh, 1993;Streeter & McBurney, 2003). Although some have questioned the universality of these findings (Marlowe & Wetsman, 2001;yu & Shepard, 1998), at least in westernized societies, women with relatively small WHRs tend to be more desired as mates (see Weeden & Sabini, 2005, for a recent review).…”
mentioning
confidence: 99%